PENGARUH MEDIA PEMBELAJARAN DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Siska Oktavera, Siska Oktavera (Pascasarjna Universitas Negeri Jakarta, 2015)
Abstract : This study aims to determine the effect of the learning media thatinclude video and picture media and self-regulated learning of the learningoutcomes of Natural Science on the content correlation between of naturalresource with environment and technology. The study was conducted on studentsin grade IV SD Negeri Karang Tengah 4 Tangerang, the number of students asmany as 36 students. Research using experiment method treatment by level 2 x 2.Data analysis is the analysis of variance of two path (ANOVA). The result of thisstudy indicate that (1) There are differences in learning outcomes of naturalscience among the group given video media and the group given picture media(2) there are interaction between learning media with self-regulated of thelearning outcomes of natural science on the content correlation between of naturalresource with environment and technology.Keywords: video media, picture media, self-regulated learning, learning outcomes of natural science.